Terrestrial invertebrates on Pulau Jarak and Pulau Lalang, straits of Malacca - Hashim, Rosli; Ramli, R.; Sofian-Azirun, Mohd; Diah, S.Z.M.; Abdullah, N.A. (Faculty of Science, University of Malaya, 2008)
Two visits to Pulau Jarak and Pulau Lalang of Straits of Malacca were carried out on 5-6 June 2004 and 23-28 November 2007 to document the diversity of selected taxa of terrestrial invertebrates. Various techniques such as sweep nets, pit-fall traps, flying intersection traps, Winkler method, light traps, and manual search (assisted by visual aid such as digital cameras and digital video-camera) were employed. There were great variations in diversity of terrestrial invertebrates inhabiting both islands. In Pulau Jarak, a single species of land-crab (Gecarcoidea lalandii), three species of butterflies, a single species of fruit fly (Bactrocera carambolae) and seventeen species of ants were recorded. In Pulau Lalang, there were three species of butterflies and twenty-four species of ants. However, the study period was too short for a comprehensive representation of terrestrial invertebrates species inhabiting the islands.